2010
DOI: 10.1002/pssc.200983473
|View full text |Cite
|
Sign up to set email alerts
|

Towards a deeper understanding of the reduced efficiency droop in low defect‐density GaInN wide‐well LEDs

Abstract: A series of 400 nm emitting GaInN/GaN single-well light-emitting diodes, grown on ultra-low dislocation density GaN templates with well widths varying between 3 and 18 nm, were investigated by pulsed and time resolved electroluminescence measurements using small signal modulation technique for the latter. A reduction of the efficiency droop at high current densities with increasing well width was observed. The highest overall external quantum efficiency was obtained for LEDs with 11 nm thick double-heterostruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…On the basis of both experimental and theoretical observations, several different mechanisms have been suggested as explanations. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, according to the proposal of carrier leakage from multiple quantum wells (MQWs) caused by the polarization field, [18][19][20][21] and based on the simulation results, the electron leakage was caused by band-bending. 3,22,23) Furthermore, electron overflow was experimentally observed by inserting an extra Mg-doped GaN/InGaN/GaN quantum well (QW) structure on the p-side of the electron blocking layer (EBL) and showed that electron overflow was bias dependant.…”
mentioning
confidence: 99%
“…On the basis of both experimental and theoretical observations, several different mechanisms have been suggested as explanations. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, according to the proposal of carrier leakage from multiple quantum wells (MQWs) caused by the polarization field, [18][19][20][21] and based on the simulation results, the electron leakage was caused by band-bending. 3,22,23) Furthermore, electron overflow was experimentally observed by inserting an extra Mg-doped GaN/InGaN/GaN quantum well (QW) structure on the p-side of the electron blocking layer (EBL) and showed that electron overflow was bias dependant.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Although the Auger loss mechanism was proposed to cause efficiency droop in experiments using an InGaN/GaN double-heterostructure ͑DH͒ active region, 5,6 it is expected to be very small in wide band-gap semiconductors and has been verified by using many body models. Many applications in the solid-state general lighting industry require high light-output power.…”
Section: Effect Of An Asymmetry Algan Barrier On Efficiency Droop In mentioning
confidence: 99%
“…8 In addition, the LED efficiency also depends strongly on the active region design and double heterostructure (DH) active regions have been shown to be more promising than conventional quantum wells (thickness < 2 nm) due to their 3D density of states. 9,10 Moreover, it has been shown that multiple thin (3 nm) DH active regions separated by low energy barriers are more promising for high material quality and high efficiency light emitters than quantum well based and also thick (more than 6 nm) DH layers. 11 Therefore, investigation of SEI effects in multi-3 nm DHs LEDs is warranted which is the subject matter of this manuscript.…”
mentioning
confidence: 99%